2022
DOI: 10.3389/fgwh.2022.859797
|View full text |Cite
|
Sign up to set email alerts
|

The More You Know, the Less You Stress: Menstrual Health Literacy in Schools Reduces Menstruation-Related Stress and Increases Self-Efficacy for Very Young Adolescent Girls in Mexico

Abstract: Improving the menstrual health literacy of girls and boys is a key strategy within a holistic framework of Save the Children's school health and comprehensive sexuality education programming. As menstrual health is an emerging area of study and programming, Save the Children continues to learn and adjust its interventions using program evaluations and rigorous monitoring. This paper will examine program-monitoring data from three cohorts, representing 47 public schools in Mexico City, Puebla, and Mérida, Mexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The scope of scientific production on access and practices of menstrual hygiene was analyzed and organized by observation of recurrence, that is, by similarity of content, emerging three categories: 1) Access to dignified conditions for MHM ( 26 , 28 - 30 , 38 ) ; 2) Need for access to information ( 14 , 28 - 33 , 36 - 37 , 39 ) ; and 3) Practices for MHM ( 27 , 31 , 34 - 35 ) . The summary of the results identified by the studies in this review is presented in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scope of scientific production on access and practices of menstrual hygiene was analyzed and organized by observation of recurrence, that is, by similarity of content, emerging three categories: 1) Access to dignified conditions for MHM ( 26 , 28 - 30 , 38 ) ; 2) Need for access to information ( 14 , 28 - 33 , 36 - 37 , 39 ) ; and 3) Practices for MHM ( 27 , 31 , 34 - 35 ) . The summary of the results identified by the studies in this review is presented in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The findings of studies on access to information showed that adolescent girls who talked to their mothers ( 26 , 30 ) and who received information in schools ( 38 ) were considered more likely to feel prepared to experience menstruation. They were also those who related menstruation to a positive experience ( 26 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Of the 31 articles that met the inclusion criteria, 26 (84%) were direct evaluations of interventions , four (13%) were systematic literature reviews of gender focused methods and evaluation tools [34][35][36][37], and one was a review of a large multi-site program [38]. Fourteen of the 26 (45%) evaluations were conducted in Sub-Saharan Africa [9][10][11][12]16,[21][22][23][24]26,28,[31][32][33] while the remaining articles focused on specific locations were split between North America (n=4) [17,18,27,29], the Middle East (n=4) [8,13,15,30], and India (n=4) [14,19,20,25].…”
Section: Overall Description Of Included Studiesmentioning
confidence: 99%
“…The most prevalent RMANCAH focus area was sexual health (n=16, 52%) [13,[18][19][20][21][22][23][25][26][27][28]30,32,33,37,38], largely concerning the issues of gender-based violence (GBV) and intimate partner violence (IPV) (n=8) [13,19,23,26,30,33,35,37] and HIV/AIDS prevention (n=8) [19,22,25,28,32,33,37,38]. Seven articles focused on maternal and neonatal health interventions [9,11,12,15,16,26,29], ten evaluated adolescent or child health and nutrition programs [8,12,[15][16][17][18]20,22,27,…”
Section: Overall Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation